Doing Theology And Our Theological Education: An Indonesian Perspective - Raymundus I Made Sudhiarsa (International Journal of Indonesian Philosophy & Theology, 2020)
The article argues that the doing theology in multi-cultural and multi-religious society expects a close collaboration of multi-disciplines. Such interdisciplinary approach makes theology possible to look at the problems of the people in a comprehensive way. The church in Indonesia has been struggling quite a lot in this theological endeavour. The International Joint Conference held in Yogyakarta, Indonesia (March 2019), was an important event of this kind. And responding the discussions at the conference, this article attempts to deal with the importance of doing theology in context and its impacts on theological educations in the country. The article then suggests everyone to revisit our traditional theological programmes and to make necessary revisions needed in responding the contemporary world. In this way the church could claim the relevance of its existence and its public theology for the goodness of the country and the betterment of the society at large.